Progression of Pulmonary Function and Correlation with Survival Following Stereotactic Body Radiotherapy of Central and Ultracentral Lung Tumors - Regnery, Sebastian (Cancers (Basel), 2020)
SIMPLE SUMMARY: Stereotactic body radiotherapy (SBRT) enables highly focused irradiation of lung tumors and has become a standard treatment. However, SBRT of lung tumors with close proximity to the central airways or mediastinum (central and ultracentral tumors) is associated with an increased risk for severe complications (bronchial bleeding, blockage of bronchi with loss of lung function). This retrospective study analyzed lung function and survival after risk-adapted approaches of SBRT in 107 central and ultracentral lung tumors. Lung function (vital capacity, forced expiratory volume in the first second) showed a statistically significant but in absolute numbers modest decrease that correlated moderately with the maximum radiation dose to the central airways. Stronger decrease in pulmonary function was found to be associated with limited survival. Consequently, lung function tests should be an integral element of follow-up after SBRT of lung tumors with proximity to the central airways or mediastinum. ABSTRACT: Stereotactic body radiotherapy (SBRT) to central and ultracentral lung tumors carries a risk of excessive toxicity. This study analyzed changes in pulmonary function tests (PFT) and their correlation with overall survival (OS) in 107 patients following central (n = 62) or ultracentral (n = 45) lung SBRT. Ultracentral location was defined as planning target volume overlap with the proximal bronchial tree (PBT). Vital capacity (VC) (−0.3 l, absolute −9.4% of predicted, both p < 0.001) and forced expiratory volume in the first second (FEV(1s)) (−0.2 l, absolute −7.7% of predicted, both p < 0.001) significantly decreased following SBRT. Higher maximum dose to the PBT significantly correlated with a steeper decline in VC (p = 0.005) and FEV(1s) (p = 0.03) over time. Pronounced decline in FEV(1s) between 6 and 12 months (HR = 0.90, p = 0.006) and pronounced decline in VC between baseline and 12 months (HR = 0.95, p = 0.004) independently correlated with worse OS. Consequently, PFT presented a statistically significant albeit clinically mild decrease in lung volumes following central and ultracentral SBRT that correlated moderately with maximum dose to the PBT. Stronger decline in pulmonary function was associated with constrained survival, advocating consequent performance of PFT during follow-up.